Gender Stereotypes in Children’s Literature (with special reference to H.Ch. Andersen’s and W. Disney’s fairytales) - Knyazyan, Anna (Armenian Folia Anglistika, 2017)
This article is devoted to the study of those concepts of masculinity and femininity that are fixed and replicated in literature. These gender stereotypes are absorbed during early childhood, when the process of gender identification takes place. We view gender identity as the process through which children acquire the characteristics, attitudes, values and behaviors that society defines as appropriate to their gender and which lead them to adopt roles and responsibilities that are prescribed to men and women. A number of stories by H.Ch. Andersen and W. Disney have been analyzed in order to determine how gender roles and sex frequency appear in children’s literaturе. It should also be noted that no theoretical reasoning and generalizations are valid unless they are corroborated and tested empirically. That is why the use of quantitative and qualitative methods of sociology in the study of gender relations is more than obvious.
Keywords: gender roles; gender stereotypes; fairytales; male; female; children’s literature